Outcomes of Breast Cancer Management from an Urban Specialist Breast Center in South India - Mullapudi, Naga Amulya; Kirti, Kabeer Katherine; Padmanaban, Naveen; Nimmagadda, Ramesh; Radhakrishna, Selvi (Indian Journal of Medical and Paediatric Oncology, 2019)
Context and Aims: The disease pattern and presentation of breast cancer in India are thought to differ from the West. The purpose of this study is to describe and to discuss the presentation, clinicopathological data, and survival from an urban specialist breast center in Southern India. Materials and Methods: Prospectively collected data were analyzed for clinicopathological details, treatment variables, and survival outcomes were analyzed. Cumulative survival curves were estimated using the Kaplan–Meier method for patients treated from 2007 to 2011. Results: A total of 1671 patients were operated at our center from January 2007 to December 2016. Average age at diagnosis was 54.2 years. Over 70% had Stage I and Stage II disease, infiltrating duct carcinoma was predominant in 88.2%. Average clinical tumor size was three centimeters. Breast conservation was performed in 22.4%. Sentinel lymph node biopsy was performed in 44.6%. Estrogen-receptor positivity was seen in 64.6%, 22.2% were Her2Neu positive. Triple negative disease was seen in 19.1%. Survival analysis was done using the Kaplan–Meier curves for 540 patients treated from 2007 to 2011. The median follow-up of surviving patients was 70 months with 10% lost to follow-up. In our study population, the 5 years overall survival rate is 88.3% and disease-free survival is 85.7%. Conclusion: Our study reflects a higher percentage of early breast cancer with outcomes comparable to the West. More research is required to understand the genetic predisposition in our population.
Keywords: Breast cancer; breast cancer in India; breast cancer management; breast cancer outcomes; specialist breast center